2022
DOI: 10.3390/ma15051886
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Performance of Headed Anchors in Steel Fiber Reinforced and Conventional Concrete in Uncracked and Cracked State

Abstract: Steel fiber reinforced concrete (SFRC) is currently the material of choice for a broad range of structural components. Through the use of SFRC, the entire, or a large portion of, conventional rebar reinforcement can be replaced, in order to improve the load-bearing behavior but also the serviceability and durability characteristics of engineering structures. The use of fiber reinforcement therefore plays a vital role in acute current and future construction industry objectives, these being a simultaneous incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…Nevertheless, in order to transmit those compressive stresses is sufficient that a circumference with diameter 1.5· D concentric to the cylinder be uncracked. That result agrees with [ 7 , 12 , 16 , 65 ].…”
Section: Preliminary Numerical Analysessupporting
confidence: 92%
See 2 more Smart Citations
“…Nevertheless, in order to transmit those compressive stresses is sufficient that a circumference with diameter 1.5· D concentric to the cylinder be uncracked. That result agrees with [ 7 , 12 , 16 , 65 ].…”
Section: Preliminary Numerical Analysessupporting
confidence: 92%
“…If the concrete is cracked, the anchors should have adequate clearance from the cracks, so that the failure mode is not dictated by cracking existing prior the installation. Where this criterion cannot be met, the shear strength of the anchor is lower than that predicted by this model, but however only moderately [ 7 , 12 , 16 , 65 ].…”
Section: Reference Structure and Scope Of The Research Workmentioning
confidence: 92%
See 1 more Smart Citation
“…Effects of the anchor head size and the concrete member thickness are investigated by Nilforoush et al 4 Specific aspects of non-standards concrete material properties are presented with respect to aggregate type in the study by Ninčevi c et al, 5 curing state in the study by Ninčevi c and colleagues, [6][7][8] the influence of low-emission concrete binders in the study by Al-Yousuf and colleagues, 7,9 and the inclusion of fiber reinforcement in the study by Spyridis and Mellios. 10 Beyond typical quasi-static loads, research has identified the performance of anchors against concrete cone breakout failure in case of external confinement/prestressing, 11,12 dynamic and seismic actions, [13][14][15][16] and fire. [17][18][19][20] The resistance is also affected, generally adversely, by the existence of cracks and reinforcement in concrete; an indepth explanation of disruption in the stress flow around and anchor due to cracking and reinforcement can be drawn from the studies by Eligehausen et al 21,22 The positive effects of supplementary hanger reinforcement in the load-bearing capacity of anchors against breakout failure, are discussed for cast-in systems considering static loads in the study by Sharma et al 23 and seismic actions in the study by Petersen et al 24 and as a strengthening method with post-installed hanger reinforcement in the study by Vita et al 25 Neupane et al 26 provides a thorough literature review with focus on tensile anchor failure, pronouncing the challenges and uncertainties of finite element modeling of anchors in concrete, particularly observing the sensitivities from the precise anchor geometry and the lack of case studies with respect to interrupted boundaries near the anchor, particularly cracks in concrete.…”
Section: Behavior Of Anchors In Tension Subject To Concrete Cone Failurementioning
confidence: 99%
“…[ 43 ] also tested steel and plastic expansion anchors in UHPC and indicated that only plastic anchors failed with pull-out and with a load increase of up to 20% in fibre concrete compared to unreinforced concretes, while the increase between normal and high-strength concrete without fibres was not shown. Extensive reviews of the current state-of-the-art on fastenings in SFRC can be found in [ 44 , 45 ]. Finally, although Refs.…”
Section: Introductionmentioning
confidence: 99%